Pengaruh Pengelolaan Kelas dan Minat Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X di SMA Negeri 8 Kota Jambi - Redi Indra Yudha (Jurnal Ilmiah Dikdaya, 2020)
This study aims to determine the description of respondents and the influence of classroom management and interest in learning on student learning outcomes on the subjects of economy class X in SMA Negeri 8 Kota Jambi. Based on data analysis on the results of research that there is a significant influence between classroom management and interest in learning of student learning outcomes on the subjects of economy class X in SMA Negeri 8 Kota Jambi. With result of model summary R = 0,067 and R Square = 0,004. In ANOVA, the value of F = 69,368 with α (sig) = 0.003. Because α (Sig) <0.05, then regression can be used to predict classroom management and interest in learning at 95% confidence level. Based on the value of B constant for X, we can make a regression equation that is Y = a + X1 + X2 = 64,046 + 0,201 + 0,291. And, for t arithmetic X1 = 2.010, and t arithmetic X2 = 2.856 then t arithmetic> t table. This means that t count> t table. This means that the results of this t test indicate that the classroom management (X1) and interest in learning (X2) have a positive and significant impact on the learning outcomes (Y) of the students of class X economic subjects in SMA Negeri 8 Kota Jambi.